Exploitation and Marginalization of Women in Online Media News - Putri, Dian Marisha; Marsella, Emma (Budapest International Research and Critics University, 2020)
The phenomenon of online media coverage is that many women's reports exploit the existence of women as objects to seek benefits from this gender, the news of the two women who are used as objects that are treated as biological satisfiers, as objects that can be harassed or even marginalized. The primary data of the study were 10 online media reports, using Nourman Fairclough's Critical Discourse Analysis tool about